APLIKASI ZAKAT BAITUL MAL INDONESIA: STUDI KASUS PENGGUNAAN APLIKASI INTERNAL UNTUK PENERIMAAN ZAKAT DI BAITUL MAL MUNZALAN - Fadlu Fadlu (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2025)
The management of zakat institutions increasingly faces challenges in enhancing effectiveness, transparency, and accountability amid the growing demand for digital-based services. This study aims to examine the implementation of the Zakat BMI (Baitul Mal Internal) application as a digital zakat collection system at Baitul Mal Munzalan Indonesia. Employing a qualitative approach with a case study design, the research explores the experiences of staff, donors, and management in utilizing the internal application. Data were collected through in-depth interviews, observations, and document analysis, complemented by secondary sources such as standard operating procedures, zakat collection reports, and relevant literature on zakat digitalization. The findings reveal that the digitalization of zakat management at Baitul Mal Munzalan has been implemented gradually while consistently adhering to Islamic principles. The Zakat BMI internal application, integrated with supporting digital tools such as Google Docs, WhatsApp, and the official website, has contributed to improved efficiency in recording transactions and enhanced transparency in reporting. Donors generally responded positively to the digital services; however, many still required assistance due to limited digital literacy and age-related constraints. The role of field teams in providing education and guidance proved critical in facilitating user adaptation, while technical challenges, particularly limited internet connectivity, were mitigated through the continued provision of direct services. This study implies that the integration of digital and manual systems can effectively support zakat management without compromising the core values of trustworthiness, honesty, and Sharia compliance. The novelty of this research lies in its empirical evidence on the use of an internal, non-public zakat application combined with simple digital platforms in a medium-scale zakat institution, offering practical insights for similar organizations planning to adopt digital solutions within a Sharia-compliant framework.